Embedding rehabilitation into cancer care continuum: an implementation study - Fary Khan; Bhasker Amatya; Alaeldin Elmalik; Krystal Song; Demi Diaz; Michael Dickinson (Journal of Rehabilitation Medicine)
Objectives: To implement and evaluate a rehabilitation-inclusive service delivery model at a tertiary cancer hospital.